PHYTOCHEMICAL STUDY, VITAMINS CONTENT AND FREE RADICAL SCAVENGING ACTIVITY OF BIXA ORELLANA L. LEAVES FROM BENIN - BOTHON, FIFA THEOMAINE DIANE; ADOVELANDE, JACQUES; AGBANGNAN DOSSA, COKOU PASCAL; AVLESSI, FÉLICIEN; Wotto, Valentin; SOHOUNHLOUE, KOKO CODJO DOMINIQUE (My University, 2018)
This paper reports metabolites content, minerals, vitamins content and radical-scavenging potential of Bixa orellana L. leaves. The phytochemical screening based on the protocols available in the literature, showed the presence of bioactive metabolites such as: polyphenols, alkaloids, saponins, tannins, steroids, anthraquinones, sterols, terpenes and reducing sugars. Flame atomic absorption spectroscopy analysis revealed that the leaves are rich in: calcium (1.56%), potassium (1.54%), magnesium (0.501%) and phosphorus (0.37%). Kjedahl method showed the richness of the leaves in total protein content (23.70 %). In contrast to their protein content, vitamins A and C content of Bixa orellana leaves is very low: 0.23 µg/g of vitamin A and 6.80 µg/g of vitamin C. Its ethanolic extract has the same IC50 as ascorbic acid for free radical scavenging activity by DPPH method. From these results, it appears that Bixa orellana leaves, in defiance of their medicinal use, can also be used in human nutrition as a source of protein and some minerals.
Keywords: Bixa orellana; DPPH; metabolites; minerals; vitamins